Universities as Partners in Primary Health Care Innovation - Henryk Majewski; Henryk Majewski (Frontiers Media S.A., 2021)
Universities have a unique role in the health ecosystem as providers of trained staff and discoverers of health innovations. However, often they sit in silos waiting for their rare blockbuster discoveries to change clinical care or seeing health services simply as future employers of their graduates or clinical trial sites. It is a transactional and targetted relationship. This present case study is of a primary health service Access Health and Community (AccessHC) in Australia and its university partner Swinburne University of Technology. Together they established a Kickstart Program which was to provide seed funding for small joint innovation projects generated by both organisations. One project exemplifies the approach. Swinburne who has a Design School was encouraged through the Kickstart Program to design a clinical waiting room of the future. This project started with a needs analysis. The written report was to inform the design. University staff linked with their internal University animations expertise to better communicate the needs analysis. The "Access me Not" animation was created, unknown to the staff at AccessHC. At initial presentation, the way the animation communicated was not imaginable by AccessHC. "Access me not" was submitted for the 2018 International Design Awards and received an honourable mention. However, the AccessHC staff saw other uses for the approach and contacted Swinburne to design a client journey animation for the newly introduced National Disability Scheme (NDIS). The co design produced an animation of immense help to parents in navigating the scheme for complex and chronic disability care and for AccessHC the scripting served as a framework to develop it new internal NDIS care systems and processes. The Swinburne team is now producing health navigation animations for the State Department of Health and Human Services. The Kickstart Program was an engagement strategy that has produced a set of health communication tools that the health service could not have envisaged and which the University could not have imagined an application. Small low risk seed funding can indeed introduce innovations and create beneficial relationships between health services and universities.